STABILISASI TANAH LIAT SANGAT LUNAK DENGAN GARAM DAN PC (PORTLAND CEMENT) - Tirta Djusman Arief (Institute of Research and Community Outreach - Petra Christian University, 2006)
Adding sodium chloride, as admixture, and Portland Cement, as stabilizer, to a very soft clay increase its plasticity index (PI), Californian Bearing Ratio (CBR), and Unconfined Compression Strength (UCS). This paper presents the results of testings done to very soft clay from Margomulyo, Surabaya. The results show a promising tendency. Anyhow a wider and comprehensive research is still needed to ensure the long-term effect of the soil stabilization. Abstract in Bahasa Indonesia : Penambahan garam (sodium chloride) dan PC (Portland Cement) meningkatkan PI (Plasticity Index), CBR (Californian Bearing Ratio), dan UCS (Unconfined Compression Strength) dari tanah lempung sangat lunak. Dalam makalah ini disajikan hasil pengujian yang dilakukan terhadap lempung sangat lunak dari daerah Margomulyo, Surabaya. Hasilnya menunjukkan kecenderungan yang menggembirakan, namun penelitian yang luas dan komprehensif masih diperlukan untuk peningkatan stabilitas tanah dalam jangka panjang.